Kontekstowy klasyfikator złożony - Jakubczyc, Janina Anna (The context ensemble classifier, 2006)
Ensemble methods are the means for difficult learning task in supervised learning. The idea is to construct a collection of individual classifiers on the basis of one learning set. This task can be accomplished by manipulation of data set or control mechanism of learning algorithm. This paper proposal is defining different learning task using context inserted in data set by manipulating the output targets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 313-322